Tingkat Pemahaman Peserta Sosialisasi Tentang Kebijakan Registrasi Barang K3l - Kusdarwati, Eny (Pusat Pendidikan dan Pelatihan Aparatur Perdagangan, 2022)
The government has issued the registration of K3L goods (Security, Safety, Health, and Environment) policy in 2019, eventhough unregistered of K3L traded goods are still exists. This is indicator of the lack of understanding of businessmen on the registration provisions of K3L goods registration due to the limited pandemic of COVID-19. The existence of a pandemic cause socialization is held by online. This research aims to find out the level of understanding of businessmen to K3L goods registration regulations through virtual socialization. The analysis method of this research is a descriptive analysis using primary data obtained from questionnaires participants of socialization. The results showed that the level of understanding of businessmen to K3L goods registration regulations amounted to 88.89%. It means most respondents has good understanding about K3L registration although disseminated by virtual.